Effects of Capital Expenditures, Development Index and Unemployment on Poverty in Gorontalo Province - Dewi Purnama Isa; Muhammad Amir Arham; Sri Indriyani Dai (Gorontalo State University, 2019)
This study aims to analyze the effect of capital expenditure in the form of regional government budgets to obtain fixed assets, the Human Development Index and Unemployment to the Poverty Level in Gorontalo Province. The data used are secondary data obtained from the Gorontalo Province Central Bureau of Statistics and the Registration Management Information System (Simreg Bappenas) during the period 2010-2015, the unit of analysis is 5 districts 1 city in Gorontalo Province. The research estimate uses panel data multiple regression analysis with the Fixed Model Effect (FEM) method. The results of the study indicate that (i) The amount of capital expenditure allocated by each region in Gorontalo Province shows a positive and significant influence on the Poverty Level in the 2010-2016 period. (ii) The Human Development Index, which is a benchmark for the achievement of an area in three basic things such as life expectancy, education level, and a decent level of life, turned out to have a positive and significant influence on the District / City Kemskinan Level in Gorontalo Province. (iii) Unemployment has a positive but not significant effect on the District / City Poverty Level in Gorontalo Province in the period 2010-2016.